Implementasi Pembelajaran Seni Tari pada Anak Tunarungu Menggunakan Model Project Based Learning di Sekolah Luar Biasa Tamansari Kota Tasikmalaya - Anggita Yulizar Nada Pratiwi; Asti Tri Lestari; Rikha Surtika Dewi (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
Learning dance for deaf children faces unique challenges due to their hearing limitations in understanding rhythm and movement. To overcome this, an exploration-based approach and direct experience are needed. This study aims to analyze the implementation of dance learning for deaf children using the Project Based Learning model at SLB Negeri Tamansari, Tasikmalaya City to improve understanding of dance concepts, movement understanding, rhythm coordination, teamwork, and responses to learning using a scientific approach with five main steps, namely observing, asking, reasoning, trying, communicating. This study uses a qualitative descriptive method with observation, interview, and documentation techniques. The subjects of the study were deaf students who took part in dance learning, from movement exploration to the final performance. This model allows them to learn actively, build understanding through direct practice, and develop creativity in performing dance. The results of the study showed that the implementation of Project Based Learning succeeded in improving the dance skills of deaf students. The use of hand clapping instructions and teacher types made it easier to understand rhythm. Repeated practice helps them adjust their movements to the tempo, while the performance increases their confidence and expression.